1990
DOI: 10.1007/bf00197927
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic foot: magnetic resonance imaging evaluation

Abstract: Fourteen diabetic patients with suspected foot infection and/or neuropathic joint (Charcot Joint) were evaluated with magnetic resonance imaging (MRI) in an attempt to assess the extent of the infection and also to distinguish infection from the changes seen with neuroarthropathy. The majority of patients with infection had more than one site of involvement and the following diagnoses were made by MRI evaluation: osteomyelitis (n = 8), abscess (n = 7), neuropathic joint (n = 5), septic arthritis (n = 4), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…In our experience, the amount and distribution of joint fluid seen on MR images may be similar in normal and abnormal ankles. This led us to believe that the fluid in the ankle seen on MR images should not be considered abnormal, as has been stated [1][2][3][4][5]. To test this hypothesis, we studied the amount and distribution of fluid seen on MR images of both normal and abnormal ankles.…”
Section: We Then Compared the Resultsmentioning
confidence: 99%
“…In our experience, the amount and distribution of joint fluid seen on MR images may be similar in normal and abnormal ankles. This led us to believe that the fluid in the ankle seen on MR images should not be considered abnormal, as has been stated [1][2][3][4][5]. To test this hypothesis, we studied the amount and distribution of fluid seen on MR images of both normal and abnormal ankles.…”
Section: We Then Compared the Resultsmentioning
confidence: 99%
“…Problems arise for the radiologist mainly because signal alterations typical for osteomyelitis are not specific. Various authors have addressed this problem of low specificity in bone marrow signal changes as a result of multiple causes such as traumatic or surgical injury, diabetic osteoarthropathy, malignancy and recent radiation therapy [2,5,13,14,15]. Nonspecific bone marrow alterations with signal loss on T1-weighted images and high signal on T2-weighted images have, for example, been shown to occur adjacent to uncomplicated septic joint effusions in up to 60 % which led to the false interpretation of concurrent osteomyelitis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been observed that chronic neuroarthropathy appears as low-intensity signal on both Tl-weighted and T2-weighted images with ill-defined joint spaces [9], acute, rapidly progressive neuroarthropathy creates high signal intensity on T2-weighted images [10,11] making it indistinguishable from osteomyelitis on non-contrast-enhanced MRI. Five cases of neuropathic disease of the foot were included in the series reported by Morrison et al [4], who studied the utility of fat-suppressed contrast-enhanced MRI for the diagnosis of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%